Synergetic effects of nano-boehmite and Y nano-zeolite on catalytic cracking of residue oil - Ehsan Amini; Kamran Ahmadi; Alimorad Rashidi; Amir Ali Youzbashi; Mehran Rezaei; Sakineh Mesgar (Scientific Reports)
Abstract Boehmite nanoparticles and NaY nanozeolite were synthesized by co-precipitation and hydrothermal methods, respectively, and characterized by XRD, FT-IR, TG-DTA, BET, and SEM techniques. XRD and BET analyses demonstrated the formation of boehmite nanoparticles with a surface area of 350 m2/g and high crystallinity NaY nanozeolite with a surface area of 957 m2/g. In order to evaluate the effect of the content of the mesoporous boehmite nanoparticles on the catalytic performance of the Residue Fluid Catalytic Cracking (RFCC) catalyst, alumina active matrix-based and silica inactive matrix-based catalysts were prepared. Results actually demonstrated that the acidity of the zeolite composition improved with the addition of boehmite nanoparticles. On the other hand, in equal zeolite content, the alumina active matrix-based catalyst possessed higher acidity (NC30B20, 3.44 mmol NH3/g catalyst) than the silica inactive matrix-based catalyst (NC30B0, 2.31 mmol NH3/g catalyst). Microactivity tests (MAT) demonstrated that, with equal zeolite content, active matrix-based catalysts exhibited higher catalytic performance than inactive matrix-based catalyst. Furthermore, the active matrix-based catalyst (NC30B20) with a surface area of 370 m2/g showed the optimum catalytic performance in the RFCC process. The synthesized NC30B20 catalyst with 20 wt% mesoporous boehmite nanoparticles as an active matrix and 30 wt% zeolite nanoparticles balanced with silica had the highest gasoline yield (42 wt%) and gasoline selectivity (65.1 wt%). The catalytic performance test results showed that in equal MAT conversion (almost 64 wt%), the synthesized NC30B20 catalyst had higher catalytic performance than the commercial catalyst.